2012
DOI: 10.1123/jsm.26.6.532
|View full text |Cite
|
Sign up to set email alerts
|

A New Age of Demand-Based Pricing: An Examination of Dynamic Ticket Pricing and Secondary Market Prices in Major League Baseball

Abstract: In 2010, the San Francisco Giants became the first professional team to implement a comprehensive demand-based ticket pricing strategy called dynamic ticket pricing (DTP). In an effort to understand DTP as a price setting strategy, the current investigation explored Giants’ ticket prices during the 2010 season. First, the relationship between fixed ticket prices, dynamic ticket prices, and secondary market ticket prices for comparable seats were examined. In addition, seat location and price changes over time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 13 publications
3
51
0
Order By: Relevance
“…Shapiro and Drayer (2012) analyzed ticket prices for 12 selected games of the San Francisco Giants in the 2010 season, the first ever year in which a whole sport stadium has been priced dynamically. They reported significant effects for both time and seating category.…”
Section: Dynamic Pricing In Sportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shapiro and Drayer (2012) analyzed ticket prices for 12 selected games of the San Francisco Giants in the 2010 season, the first ever year in which a whole sport stadium has been priced dynamically. They reported significant effects for both time and seating category.…”
Section: Dynamic Pricing In Sportsmentioning
confidence: 99%
“…Shapiro and Drayer (2014) as well as Shapiro and Drayer (2012) reported that ticket prices increased continuously towards the day of the match with the application of a DTP system. Yet, a study about consumer expectations revealed that sport fans expected lower ticket prices as the time before the event decreased (Dwyer, Drayer, & Shapiro, 2013).…”
mentioning
confidence: 96%
“…The time from buying the ticket to the starting time of the game is a significant control variable for ticket prices [6]. Two forms of time multiplier are considered, and the behavior of the multipliers is shown in Figures 2 and 3.…”
Section: Time Multipliermentioning
confidence: 99%
“…Rascher et al [4] posit that Major League Baseball (MLB) teams could have increased ticket revenues by about 2.8% if they used variable ticket pricing. Dynamic pricing appears to be a promising strategy to optimize ticket prices [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Academics and practitioners have investigated the application of RM techniques to those other areas. Industries that now apply RM methods include spectator sports (Shapiro and Drayer, 2012), theatre (Healy, 2011;Jones, 2012), foodservice (Hayes and Miller, 2011;Heo, 2013;Heo et al, 2013;Kimes and Beard, 2013), parking (Cooper and McGinty, 2012;Shoup, 2011), taxi and limousine service (Lowrey, 2014;Zhao, 2016), mobile gaming (Murphy, 2015) and many others. Nevertheless, academic applications of RM to the theme park industry have been extremely limited (Heo and Lee, 2009).…”
Section: Introductionmentioning
confidence: 99%